The Effect Of Brand Import, Fashion Lifestyle Thriff Shop To Buying Interest (Case Study Of Universitas Muhammadiyah Bengkulu Students) - Wanda Setiawan; Mimi Kurnia Nengsih (Journal of Indonesian Management, 2024)
on purchase intention (Case Study on Students of Muhammadiyah University of Bengkulu)". This research is a quantitative study, focusing on measuring data and statistical objects through calculations. The population in this study is students of Muhammadiyah University of Bengkulu. Sampling technique was done through purposive sampling, and data collection was conducted using a questionnaire, resulting in a sample size of 100 respondents for the sake of convenience, although initially 96 respondents were targeted. The results of this study indicate that: (1) There is a positive influence of the imported brand variable on purchase intention. Based on the partial test results, a t-value of 2.947 and a regression coefficient of 0.111 were obtained with a significance level of 0.000. (2) There is a positive influence of the fashion lifestyle thrift shop variable on purchase intention. Based on the partial test results, a t-value of 10.406 and a regression coefficient of 0.877 were obtained with a significance level of 0.000. (3) Imported brands and fashion lifestyle thrift shops have a positive influence on purchase intention. This is evidenced by the obtained F-value of 99.238 compared to the F-table value of 1.984, with a significance level of (0.001 < 0.05).